Risk assessment on landscape development using geographic information system - Hashim, Mazlan; Okuda, Toshinori (National Institute for Environmental Studies, Japan, 2003)
This study reports on the preliminary development of risk assessment on impacts on landscape development in Pasoh Forest Region. The Geographic Information System were in the assessing such impacts where main data input are obtained from information derived from multitemporal Landsat TM data acquired since 1986. Tree census information collected from the corresponding area was used in verifying impacts at selected sites.